SIMULATION IN SAUDI HEALTHCARE: AN EMPIRICAL STUDY REVEALING THE CURRENT STATUS AND FUTURE PROSPECTS - Alrabghi, Abdullah (The South African Journal of Industrial Engineering, 2020)
Providing efficient healthcare is more important today than ever before. Simulation is a well-established technique that has been used to understand and improve systems in various applications. It seems that simulation implementation in the healthcare industry is surrounded by a number of issues. Research on the subject has been mostly restricted to the analysis of academic literature, with a few industrial surveys. This empirical study contributes to our understanding of simulation application in Saudi healthcare services. The findings include an analysis of performance improvement methodologies currently in use, as well as simulation applications, barriers, and potential.